2022
DOI: 10.1002/ca.23893
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the morphology and composition of the lumbar paraspinal and psoas muscles and lumbar intervertebral motion in chronic low‐back pain: An exploratory study

Abstract: Muscles of the lumbar spine play an important role in controlling segmental intervertebral motion. This study aimed to evaluate the association between lumbar intervertebral motion and changes in lumbar morphology/composition in people with chronic low-back pain (CLBP). A sample of 183 patients with CLBP participated in this cross-sectional study. Participants underwent lumbar flexion-extension X-rays to determine vertebral motion (translational and/or rotational motion) of lumbar levels (L1-L2 to L5-S1) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The results of our study showed L4-L5 ES hypertrophy in patients with clinical LSIs, but not in other CNLBPs, which appears to be a compensatory response of an unstable spinal system. Consistent with our findings, a recent study reported a significant increase in erector spinae CSA in patients with positive structural LSI [ 19 ]. Previous studies of spondylolisthesis also showed hypertrophy of ES [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of our study showed L4-L5 ES hypertrophy in patients with clinical LSIs, but not in other CNLBPs, which appears to be a compensatory response of an unstable spinal system. Consistent with our findings, a recent study reported a significant increase in erector spinae CSA in patients with positive structural LSI [ 19 ]. Previous studies of spondylolisthesis also showed hypertrophy of ES [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to histological studies, the deep fibers of the MF muscle contain a higher percentage of type l fibers compared to other paraspinal muscles, and these slow-twitch fibers are more exposed to the adverse effects of pain and spinal immobility. This problem is one of the causes of the MF atrophy in the present study[ 15 , 19 ]. In this study, both groups of CNLBP with and without LSI showed almost similar MF atrophy.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…From 1999 to 2016, its prevalence was reported to have increased 23.5% in China [2]. CLBP is significantly associated with the lumbar muscles [3][4][5]. Various lumbar muscles contribute to maintaining the stability of the low back during trunk movement.…”
Section: Introductionmentioning
confidence: 99%